Oxygenator Is the Main Responsible for Leukocyte Activation in Experimental Model of Extracorporeal Circulation: A Cautionary Tale. (4th May 2015) - Rungatscher, Alessio; Tessari, Maddalena; Stranieri, Chiara; Solani, Erika; Linardi, Daniele; Milani, Elisabetta; Montresor, Alessio; Merigo, Flavia; Salvetti, Beatrice; Menon, Tiziano; Faggian, Giuseppe
Abstract : In order to assess mechanisms underlying inflammatory activation during extracorporeal circulation (ECC), several small animal models of ECC have been proposed recently. The majority of them are based on home-made, nonstandardized, and hardly reproducible oxygenators. The present study has generated fundamental information on the role of oxygenator of ECC in activating inflammatory signaling pathways on leukocytes, leading to systemic inflammatory response, and organ dysfunction. The present results suggest that experimental animal models of ECC used in translational research on inflammatory response should be based on standardized, reproducible oxygenators with clinical characteristics.